PENGEMBANGAN DAN VALIDITAS E-MODUL INOVATIF NONLOGAM OKSIGEN DAN SULFUR BERBASIS KKNI - Elsa Febrina Tarigan; Nurfajriani Nurfajriani; Zainuddin Muchtar (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
The development of teaching materials must pay attention to the prerequisites of the National Education Standards Agency (BSNP) and under the curriculum in universities to achieve subject learning. Educators make innovations to create interesting sources of teaching materials. This research aims to produce an innovative e-module for non-metallic oxygen and sulfur. This study uses the ADDIE model where only three stages are used, namely Analysis, Design, and Development. The data collection instrument used a validation questionnaire per the BSNP given to material and media expert validators. The results showed that the electronic feasibility test of the KKNI-based modules (Indonesian National Qualifications Framework) that had been developed obtained average content feasibility of 3.49 (valid), language eligibility of 3.67 (valid), presentation eligibility of 3.62 (valid), and eligibility Graphics is 3.66 (valid) with an overall average of 3.56 which is included in the valid category which can be used as non-metallic oxygen and sulfur teaching materials based on KKNI. Keywords: e-Modules, Innovative Chemistry, Teaching Materials.